1997
DOI: 10.1111/j.1365-246x.1997.tb04501.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal thickening under the palaeo-meso-Proterozoic Delhi Fold Belt in northwestern India: evidence from deep reflection profiling

Abstract: S U M M A R YThe results of deep reflection profiling studies carried out across thy palaeo-mesoProterozoic Delhi Fold Belt (DFB) and the Archaean Bhilwara Gneissic Complex (BGC) in the northwest Indian platform are discussed in this paper. This region is a zone of Proterozoic collision. The collision appears to be responsible for listric faults in the upper crust, which represent the boundaries of the Delhi exposures. In these blocks the lower crust appears to lie NW of the respective surface exposures and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…This movement, along with plate margin geometry, gives rise to the unusual lobate shape of the Sulaiman Lobe and Range at this boundary (e.g., Haq and Davis, 1997;Bernard et al, 2000). In the north, bidirectional subduction of Indian and Eurasian continental lithosphere occurs where the plates meet beneath the 55Њ 60Њ 65Њ 70Њ 75Њ 80Њ 25Њ 30Њ 35Њ 40Њ Holt and Wallace, 1990Mellors et al, 1995Roecker et al, 1993Hearn and Ni, 1994Priestley, 1997Mangino & Priestley, 1998Byrne et al, 1992Davis and Lillie, 1994Gabriel and Kuo, 1966Banks and Warburton, 1986Lillie et al, 1987;Jadoon et al, 1996Jadoon et al, , 1994; Khurshid, 1991Tewari et al, 1997Kulagina et al, 1974Jadoon & Khurshid, 1996Lillie et al, 1987Searle & Tirrul, 1991Molnar, 1988Lyon-Caen & Molnar, 1984Mishra, 1982Yegorkin & Matushkin, 1970Ryaboy, 1969Singh et al, 1999Priestley, 1997 Krishna andRamesh, 2000;Krishna et al, 1999 Pamirs and Karakorum (e.g., Molnar, 1988;Fan et al, 1994). Subduction of the Arabian plate beneath southwestern Pakistan produced the Makran accretionary wedge evidenced in the east-west trending Makran Range.…”
Section: Tectonic Settingmentioning
confidence: 96%
“…This movement, along with plate margin geometry, gives rise to the unusual lobate shape of the Sulaiman Lobe and Range at this boundary (e.g., Haq and Davis, 1997;Bernard et al, 2000). In the north, bidirectional subduction of Indian and Eurasian continental lithosphere occurs where the plates meet beneath the 55Њ 60Њ 65Њ 70Њ 75Њ 80Њ 25Њ 30Њ 35Њ 40Њ Holt and Wallace, 1990Mellors et al, 1995Roecker et al, 1993Hearn and Ni, 1994Priestley, 1997Mangino & Priestley, 1998Byrne et al, 1992Davis and Lillie, 1994Gabriel and Kuo, 1966Banks and Warburton, 1986Lillie et al, 1987;Jadoon et al, 1996Jadoon et al, , 1994; Khurshid, 1991Tewari et al, 1997Kulagina et al, 1974Jadoon & Khurshid, 1996Lillie et al, 1987Searle & Tirrul, 1991Molnar, 1988Lyon-Caen & Molnar, 1984Mishra, 1982Yegorkin & Matushkin, 1970Ryaboy, 1969Singh et al, 1999Priestley, 1997 Krishna andRamesh, 2000;Krishna et al, 1999 Pamirs and Karakorum (e.g., Molnar, 1988;Fan et al, 1994). Subduction of the Arabian plate beneath southwestern Pakistan produced the Makran accretionary wedge evidenced in the east-west trending Makran Range.…”
Section: Tectonic Settingmentioning
confidence: 96%
“…1b). Structure and tectonics along this transect were discussed in earlier papers (Tewari et al, 1997;Vijaya Rao et al, 2000), especially the broad structural features of both these fold belts. They essentially discussed the reflectivity characteristics to distinguish various tectonic domains in the region as well as the crustal thickness in each of them.…”
Section: Introductionmentioning
confidence: 98%
“…The extensive deep seismic sounding (DSS) studies carried out over the Cambay basin for hydrocarbon exploration (Kaila et al 1990;Tewari et al 1991Tewari et al , 1997Dixit et al 2010) revealed major structural trends in the basin and supported the explanation of magmatic underplating beneath the Kutch and Cambay rift basins. The Cambay basin is complex in nature, containing horst structures and E-W directional faults that divide the basin into four sub-basins.…”
Section: Geophysical Studiesmentioning
confidence: 99%